1984
DOI: 10.2134/jeq1984.00472425001300020022x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Trapping by Sediment Deposition in a Seasonally Flooded Lakeside Wetland

Abstract: Sediment and nutrient retention was studied in a seasonally flooded lakeside wetland as a natural mechanism for preventing water quality deterioration. Both wetland and upland soils in the watershed had comparable concentrations of inorganic P on a per‐volume basis, while NH4+‐N and organic forms of N and P were much higher in the wetland soils. Nitrate concentrations expressed in a per‐volume basis were lower in the wetland soils than in the upland soils.The distribution of sediment and nutrients in the wetla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
2
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(60 citation statements)
references
References 0 publications
2
55
2
1
Order By: Relevance
“…Many of the studies which recorded over 90% N reduction appear to have been conducted on a regular weekly or monthly sampling strategy (Baker and Maltby, 1995;Haycock and Pinay, 1993;Pinay and Decamps, 1988) or avoided sampling during high flow events (Cooper, 1990). Those studies that recorded relatively low N reduction (<50%) or highly variable N reduction were often those that were conducted daily (Cooper, 1994;Jordan et al, 2003) or sampled more regularly during high flows (Raisin and Mitchell, 1995;Brunet et al, 1994;Daniels and Gilliam, 1996), or sampled from many locations within the wetland (Johnston et al, 1984). This is also the case in some of the studies which found relatively low P reduction or variable P reduction (Raisin and Mitchell, 1995;Spangler, 1977;Jordan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the studies which recorded over 90% N reduction appear to have been conducted on a regular weekly or monthly sampling strategy (Baker and Maltby, 1995;Haycock and Pinay, 1993;Pinay and Decamps, 1988) or avoided sampling during high flow events (Cooper, 1990). Those studies that recorded relatively low N reduction (<50%) or highly variable N reduction were often those that were conducted daily (Cooper, 1994;Jordan et al, 2003) or sampled more regularly during high flows (Raisin and Mitchell, 1995;Brunet et al, 1994;Daniels and Gilliam, 1996), or sampled from many locations within the wetland (Johnston et al, 1984). This is also the case in some of the studies which found relatively low P reduction or variable P reduction (Raisin and Mitchell, 1995;Spangler, 1977;Jordan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Wetlands reduce nutrients by encouraging sedimentation (Karr and Schlosser, 1978;Johnston et al, 1984), sorbing nutrients to sediments (see Khalid et al, 1977), taking up nutrients in plant biomass (Lee et al, 1975) and enhancing denitrification (Lowrance et al, 1984). While the evidence for this arises from a number of separate studies, some studies show that wetlands can be ineffective at reducing nutrient loadings, or might even increase nutrient loadings.…”
Section: How Can Wetlands Change Nutrient Loads?mentioning
confidence: 99%
See 1 more Smart Citation
“…In a eutrophic lake, the retentate contained abundant nutrients, which would enrich the riparian zone (Johnston et al, 1984). In the littoral, especially where there is a macrophyte cover, sediments carried by lake currents also may settle.…”
Section: External Sources Of Nitrogen In the Littoral Zonementioning
confidence: 99%
“…Finer suspended or resuspended sediment with abundant labile nutrient and absorbed pollutants (Naiman & Dé camps, 1997) carried by flowing water enrich riparian sediments proportionally (Johnston et al, 1984). Whether riparian zones will be a sink or source to open water is not clear.…”
Section: Introductionmentioning
confidence: 99%